The “Co-financing” of PPPs: Concept, Nature, Evolution and Experiences - Paz Sime, Miguel Angel (2017)
The evolution of the State’s role in the economy finds its most significant expression in the new role of guarantor and regulator it has taken against the old borrowing and interventionist role that characterized it. In this context, the State uses the Public Private Partnerships, in order to be able to solve the problem derived from the need to execute socially profitable projects but not economically. The author will develop the concepts of co-financing and co-financed PPPs; as well as presenting practical cases of this method of financing public services and infrastructure projects.